Święty Aleksy na scenie pijarskiego kolegium w Górze Kalwarii - Mieszek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The article presents the art of Piarist college of Góra Kalwaria, the theme of which was life of st. Alex. The medieval story has been adjusted to Baroque imagination and aesthetics.